Medidas de proteção contra a infecção pelo Zika vírus por gestantes - Melo, Vladimir Antonio Dantas (2018)
The emergence of Zika virus was accompanied by tragic consequences, especially for pregnant women, due to its association with the birth of newborns with microcephaly. The lack of vaccine or specific treatment led to actions of the public agencies for the implementation of preventive measures to control the infection by Zika virus. Based on this assumption, the purpose of this study was to evaluate whether pregnant women in the municipality of Propriá-SE adopted individual protection measures recommended by the Ministry of Health as a way to protect themselves from infection and prevent the birth of infants with microcephaly. To collect the data, an individualized interview was conducted with 177 pregnant women registered by SUS, through a semi-structured form, during the prenatal care at the Health Post in both urban and rural areas of the municipality. The research lasted four months, starting in November 2016 and after the previous two pilot tests. Data analysis was performed using descriptive statistics, Chi-square test, logistic regression and the magnitude of the association was measured by OddsRatio. The use of repellents was reported by 57% of pregnant women, the change in dressing by 44%, the use of 47% nets and 7% protection screens. Both the media and the guidance of health professionals contributed to a better understanding of the pathology and adoption of care, including the use of repellents. Three factors contributed to the adherence to preventive measures by pregnant women: Professional and / or media orientation, schooling and visualization of a baby with microcephaly. The low socioeconomic status of pregnant women was the main impediment to adherence to personal protection measures.